WAYANG KULIT MANUSIA ANTARA MITOS DAN KENYATAAN - Otok Herum Marwoto (Institut Seni Indonesia Yogyakarta, 2012)
A religious traditional art in society is related to myth which can be categorized intofolktale. This tradition has been often become one in the Javanese mind and influential ingiving direction to their lives. Concerning with myth is inseparable from people’s believed. Thepeople believe which is appearing is usually established on the basis of a tale or story, which isdescendant from the local people and unwritten but believed by the society so that it becomestradition and culture encouragement. One of Indonesian ancestors’ heritages is leather puppetwhich can be enjoyed by us until now, although the form and the development conform to thedevelopment of the present modern world.Myth of the leather puppet in Javanese people themselves has been an icon, becausethe leather puppet it selves becomes myth which unified with tradition as well as Javanesepeople culture. So, other myth follows the leather puppet myth. One of the existing myths insociety are the myth’s appearances of human’s skin puppet, mainly a traditional art of leatherpuppet the material of which is believed to be created from human’s skin.Kedakan village located in the slope of Merbabu valley which is remote and far fromthe city. Because of its remote location, this place leave culture heritage of the preservedancestor’s tradition, such as human’s skin puppet. The appearing myth in the human skinpuppet is that of believed that the puppet is created from human’s skin, therefore, the puppetis considered holy and highly respected. The sacredness of the puppet appears, since manymisterious and illogical things happened related to the sacred puppet frequently. The mythwhich are still being preserved enables this leather puppet art in the remote village ever lastingand the existence is still being nurtured.Key words: Leather Puppet, Human Skin, and Myth